PENGARUH DISIPLIN SISWA TERHADAP HASIL BELAJAR SISWA KELAS XI SMK MUHAMMADIYAH 2 PEKANBARU - Putri Clawson; Tri Listia Dewi (P3M STKIP 'Aisyiyah Riau, 2015)
The purpose of this study was to find out the influence of student discipline on the learning outcomes of class XI economics at SMK Muhammadiyah 2 Pekanbaru. This research was also carried out at SMK Muhammadiyah 2 Pekanbaru. In this study the authors used a questionnaire as a tool to collect data and student learning outcomes. And the sample used was 30 students of SMK Muhammadiyah 2 Pekanbaru. In processing data, the author uses Microsoft Office Excel 2010. The results of research conducted indicate that there is an influence of student discipline on economic learning outcomes of class XI at SMK Muhammadiyah 2 Pekanbaru. Seen from the results of the t test where t Calculate> t Table (4.211> 2.048). This figure shows the influence of student discipline on the learning outcomes of class XI economics at SMK Muhammadiyah 2 Pekanbaru. While the regression test also shows the value of R2 Deternination Coefficient is 0.388. Student discipline has a contribution or influence on student economic learning outcomes of 38.8% while the other 61.2% is by other factors not included in this study.